Portrait Of A Father - Warren, Robert Penn, 1905-1989 (Book collections on Project MUSE., 2015)
One of America's great poets writes of his father, lost through death and discovered again through insistent recollection. A death in the family forces a re-sorting and reshaping of all that we can recall of times and people gone from us as we measure our identities by their remembered images. While prowling in the past, Warren is drawn to likenesses between himself and his father, between himself and others of his family. The poet finds that his father too, in his long silent youth, ventured into the writing of poetry, as have so many, but in time put it away for other things. Gradually this.